Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
DERIVADASFunciones no compuestas:                 2 2                                                    x 4 3x 2    3 6  ...
Derivación logarítmica                                                                                 x1) y = x          ...
Upcoming SlideShare
Loading in …5
×

Ejercicios derivadas

1,667 views

Published on

  • Be the first to comment

  • Be the first to like this

Ejercicios derivadas

  1. 1. DERIVADASFunciones no compuestas: 2 2 x 4 3x 2 3 6 1 31) f ( x) = 3 x + x − x + 33 x 3) f ( x) = x x + − 3 2) f ( x) = + −2− + 3 2 3 4 2 x x x x x3 x 2 3x 2 4 x − 2 x x 14) f ( x) = 6) f ( x) = x ln x − 3 5) f ( x) = x 2 senx + x cos x tgx 4 5 x 3 x ctgx7) f ( x) = 3 2 − ex 8) f ( x) = e x senx + e x cos x 9) f ( x) = 4 x arcsenx x 5x − 2 x + ex10) f ( x) = x arctgx 11) f ( x) = 12) f ( x) = 4x 2 − 1 x − ex x − arctgx x x + ln x13) f ( x) = 14) f ( x) = 15) f ( x) = arcsenx 1 − arctgx x3 senx + cos x tgx − ctgx 1 ln x16) f ( x) = 17) f ( x) = 18) f ( x) = + 2 ln x − senx − cos x xsenx x x 3 x senx19) f ( x) = xe x senx 20) f ( x) = 21) f ( x) = xe x ln xFunciones compuestas: 1 (1) y = 4 x 3 + 6 x − 2 ) 17 2) y = x 4 − 3x 2 + 6 3) y = 3 x −5 2 4) y = ( senx − cos x ) 5 15) y = x ( arctgx ) 3 ( 6) y = 1 − x 2 ) ( arcsenx) 5 3 7) y = ( 2 x + 1) 3 8) y = sen3 x + sen 2 3 x x + cos x9) y = cos 3 x − cos ( x 3 ) 10) y = ln ( senx) 11) y = log sen ( x ) 12) y = x − cos x 3  sen5 x + cos 5 x  1 1− x13) y = arcsen 1 − x 2 14) y =   15) y = arccos 1 − 16) y = arctg  sen5 x − cos 5 x  x2 1+ x17) y = arcsen x2 −1 x2 18) y = arcsen 1 − e x ( ) ( 19) y = ln e x + e 2x − 1 ) 20) y=x e 5 − 1 x6 1 arcsen   1 − cos 2 x21) 22) y = ln 23) y = arcsen (1 − x) + 2x − x 2 y =8 x 1 + cos 2 x  x  x24) y = a 2 − x 2 + a ⋅ arcsen   25) y = x a − x + a arcsen   2 2 2 a a26) y = arcsenx 1− x 2 27) y = x 2 x 2 − 4 − 2 ln x + x 2 − 4 ( ) 28) y = ln x + x 2 + 1 ( ) x   1 − x 29) y = ln ( arcsenx) + arcsen (ln x) 30) y = arcsen 31) y = ln  ln  ln    1+ x   1 + x  2   (32) y = sen 2 sen 2 sen 2 x ( )) 33) y = cos   1  arccos ( senx)  34) y = x+ x+ x 35) y = arctg tg 2 x ( )  
  2. 2. Derivación logarítmica x1) y = x 3x 2 2) y = x x 3) y = x 1 x4) y =  1  senx 5) y =  6) y = 1 + 1   x ln x   x  x ( x + 2) 97) y = x xx 8) y = 3 x ( sen x ) 5 2 7 x3 9) y = ( x − 3) 7 ( x + 8) 11 (1 − cos x ) 7 tg 3 x 1 − x sen 3 x ln x 5 x310) y = 11) 12) x 4 5 ( arcsenx ) 3 x 2 + 13 senx x2 + 3

×